ENHANCING LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING MODEL GROUP INVESTIGATION ON 5th GRADE STUDENTS - Andrianik, Dian; Kristin, Firosalia (Universitas Pendidikan Ganesha, 2017)
This study aims to apply learning model of Group Investigation type in improving the science learning outcomes of 5th grade students of SD Negeri 04 Jambangan. This type of research is a classroom action research using the Spiral Kemmis and Robin Mc Taggart model. This study consisted of 2 cycles, with 3 meetings in each cycle. The subjects of this study were 29 students of SD Negeri 04 Jambangan. The data collection instrument uses both test and non-test techniques. The research instrument is a matter of multiple choice tests, and teacher observation sheet and students’ response. The result of the research shows that students’ cognitive, affective, and psychomotor learning outcomes are improved after the application of cooperative learning model with Group Investigation. Thus, it can be concluded that the model can improve science learning outcomes.